Postural blood pressure changes in the elderly: orthostatic hypotension and hypertension - Kocyigit, Suleyman Emre; Erken, Neziha; Dokuzlar, Ozge; Dost Gunay, Fatma Sena; Ates Bulut, Esra; Aydin, Ali Ekrem; SOYSAL, PINAR; SOYSAL, PINAR; IŞIK, AHMET TURAN (My University, 2020)
Objectives Orthostatic hypotension is a well-known disorder, but orthostatic hypertension (OHT) still remains unclear in older adults. The aim of this study was to determine the comparison orthostatic hypotension with OHT according to fall risk and geriatric assessment parameters. Methods A total of 741 patients who were admitted to the geriatric clinic and underwent comprehensive geriatric assessment were reviewed. Orthostatic blood pressure changes were measured by head-up-tilt Table test within the first three minutes. Orthostatic hypotension was defined as 20 or 10-mmHg drop in systolic and/or diastolic blood pressure from supine to standing position. OHT was defined as an increase in systolic blood pressure of 10 mmHg or more while the patient was standing up from the supine position. Results The mean age was 75 +/- 8 and 65. About 65% of all participants were female. The rate of orthostatic hypotension and OHT was 17.3 and 7.2%, respectively. The falls and dementia were more frequent, and the Instrumental Activities of Daily Living (IADL) score was lower in orthostatic hypotension group than in OHT and control groups (P 0.05). The rates of falls [odds ratio (OR) = 2.02; 95% confidence interval (CI), (0.94-4.33);P = 0.044] and dementia [OR = 2.65; 95% CI, (1.08-6.48);P = 0.032] in orthostatic hypotension group were still higher than in OHT group, even after adjusting for age, sex, estimated glomerular filtration rate and drugs. Conclusion Orthostatic hypotension may be more significant in terms of falls, dementia and impaired IADLs scores in older adults than in OHT and control groups. It seems that OHT may be of no clinical importance in geriatric practice.